In Vivo Anti-Inflammatory Potential, Minimum Inhibitory Concentration And Minimum Bactericidal Concentration Of Ferulic Acid, Isolated From Pineapple Waste (Applied Biological Research, 2023)
Compounds isolated from organic waste are used as a source for the discovery  of new entities against inflammation. Pineapple peel, a by-product of pineapple  processing industry, is a thrown away waste. The current work aimed to study  the in-vivo anti-inflammatory potential and determination of minimum  inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of ferulic acid - a phenolic acid isolated from the pineapple peel.  Pseudomonas aeruginosa (ATCC 27853), Klebsiella pneumoniae (ATCC 700603),  Bacillus cereus (ATCC 10876) and Staphylococcus aureus (ATCC 33591) were  used for MIC and MBC study. Acute toxicity screened after giving graded doses  of ferulic acid and analysed it’s in vivo anti-inflammatory potential using  carrageenin induced paw oedema and xylene induced ear oedema in Wistar rats.  NaCl and Indomethacin were used as both negative and positive controls,  respectively. The isolated phenolic compounds significantly reduced  inflammation at all the dose tested. From the study it may be concluded that the  phenolic compound isolated from pineapple peel exhibit significant anti inflammatory activities and display strong bactericidal potentiality against Staphylococcus aureus and Pseudomonas aeruginosa indicating its anti inflammatory and bactericidal potential.
Keywords: Ferulic acid; in-vivo anti-inflammatory potential; pineapple waste; Pseudomonas aeruginosa; Staphylococcus aureus